-2(d-4)=12

Simple and best practice solution for -2(d-4)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(d-4)=12 equation:


Simplifying
-2(d + -4) = 12

Reorder the terms:
-2(-4 + d) = 12
(-4 * -2 + d * -2) = 12
(8 + -2d) = 12

Solving
8 + -2d = 12

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -2d = 12 + -8

Combine like terms: 8 + -8 = 0
0 + -2d = 12 + -8
-2d = 12 + -8

Combine like terms: 12 + -8 = 4
-2d = 4

Divide each side by '-2'.
d = -2

Simplifying
d = -2

See similar equations:

| (4x+5)-(3x)= | | 7x-18=x+11 | | (7n-2)(5n-4)= | | 2x+7854.5=50000 | | 5(2x-10)= | | 15(v+2)-3v=3(4v+3)-14 | | (1/x^2)=95 | | 20x^3-1=0 | | (x+6)(8x-1)=0 | | 23=23/x | | 5-d=-11 | | 225=-8x-7(1+3x) | | 23/x=23 | | 5k^2+17k-20=-8 | | 2(c-9)=4 | | 7K=-91 | | 3y-2y=16 | | -x+16=3x+4 | | 5x^4-x=0 | | 3=z-4/2 | | 170-(160-x)+x=180 | | 2[2(6x+3)-5(2x-4)]= | | 3(x-3)-x=5 | | 6x+1=4x-30 | | 7=p*4+8 | | -2(c+18)=-8 | | 5x-23=56 | | X+8+6x=-69 | | -x+23=x+7 | | d/dx(f(3x^2)) | | -6x-12=4(2x-3) | | (x^4)^-1/4 |

Equations solver categories